The last Glauber: notes about travel, photography and memory in Diário de Sintra film - Elane Abreu; Marcelo Carvalho (Intexto, 2012)
How to differ the traveller from the exiled person? How to think the memory created in exile? These are the axes by which we turn Diário de Sintra film (2008), by Paula Gaitán, around. The film is a poetic account of Glauber Rocha's exile at this city, where photographs serve as mnemonic guide for the search of moviemaker's passage vestiges by Sintra. The film consists in an exercise of living in frontier, formation place of a fragmented, unfinished and precarious memory.